Pengaruh Briefing Dan Peran Pemimpin Terhadap Kinerja Karyawan PT. PLN (Persero) ULP Indralaya - Wahyuni, Sri; Darmawati, Tri; Heryati, Heryati (Peneliti.net, 2024)
This study aims to test the hypothesis of the influence of briefings and the role of leaders on the performance of employees of PT. PLN (Persero) ULP indralaya. The research method used is associative quantitative. The population of this study were 48 employees of PT PLN (Persero). The sampling technique is Probability sampling random sampling technique. Sources and data collection techniques of this research are primary data by distributing questionnaires to respondents and secondary data by collecting documentation and literature studies relevant to the research. The data analysis techniques used are normality test, heteroscedasticity test and multicolonierity test. The hypothesis tests used are the t test and the F test. The t test results obtained on the significant value of the briefing variable of 0.040, the variable role of the leader of 0.004, then partially concluded to be influential. While the results of the F test sig. value on employee performance is 0.000, then briefing and the role of the leader have a joint or simultaneous effect on employee performance.